Asean Integration In Improving Indonesian Women Education: A Literature Review - Rostiena Pasciana; Ieke Sartika iriany (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2018)
The Association of Southeast Asian Nations (ASEAN) is an organization of countries in Southeast Asia established in Bangkok, Thailand, on August 8, 1967 under the Bangkok Declaration by Indonesia, Malaysia, Philippines, Singapore, and Thailand. For more th an five decades ASEAN has experienced many positive and significant developments towards a more integrative and forward - looking stage with the establishment of an ASEAN Community by 2015. The ASEAN Community not only affects the economic sector, but also other sectors, including "education" as an effort to build competitive human resources. The ASEAN Economic Community (AEC) challenges in education that will be faced are the proliferation o f foreign educational institutions, standardization of orientation in education, which is pro - market, and markets labor that will be flooded by foreign workers. Therefore, the era of ASEAN free trade should be welcomed by the world of education quickly, so that the human resources (HR) of Indonesia, especially by women who still have low resource. They should be prepared for facing an intense competition with other countries. ASEAN countries have considered synchronizing the certification standards, streng thening, and improving the skills and knowledge of ASEAN youth and women in the regional integration process. Therefore, ASEAN countries have always been active in encouraging cooperative relations in various levels of education and training, at the same t ime encouraging all organizations and schools in each country to seek cooperation partners in other countries of the ASEAN region.